Estudio de factibilidad para producir y comercializar el almidon de yuca con fines de ser aprovechado por la industria de la panaderia en la ciudad de Ventanas año 2013 - Ortega Solórzano, Diogenes Edison (2014)
The study on the feasibility project to install a producer and marketer of cassava starch in the canton Ventanas Company analyzes the aspects of market, technical, and economic and financial profitability. The first part of the investigation reached the study of the product, analyzing from the definition thereof, demand analysis, and its projection, analysis of supply and its projection, analysis of price and marketing channels. Upon completion of this first part the conviction of the current scenarios of the consumer market of cassava starch for deciding on whether to invest in the installation of the plant, from the point of view of their allowed claim is obtained. The second part consisted of the technical design of the plant, which involved determining the location, size, number and type of each of the machinery and equipment required for the process, organizational, and legal regarding your property. The third part of an economic study of all operating scenarios that were established early in the technical study, among others, the initial investment, total operating costs, working capital, financing, balance sheet, income statement , ran point balance. In short in this part tried to get all the figures needed to carry out the economic evaluation. The fourth treatment on the economic evaluation of investment profitability checking on visibly defined, such as NPV (net present value) and IRR (internal rate of return) criteria. Finally overall conclusions and recommendations for the entire project based on data and measurements made in each of its parts is presented.